Renal denervation: can we press the “ON” button again in 2020? - Kądziela, Jacek; Warchoł-Celińska, Ewa; Prejbisz, Aleksander; Januszewicz, Andrzej; Witkowski, Adam; Tsioufis, Konstantinos (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2020)
In December 2018, an article summarizing available results of randomized studies on renal denervation (RDN), entitled “Renal denervation: can we press the ON button again?” was published in the Advances in Interventional Cardiology. Since then, several positive reports, including SPYRAL HTN OFF-MED Pivotal trial have been presented. In the current review the authors discuss the latest data on RDN in arterial hypertension treatment and try to answer the burning question: can we press the ON button again in 2020? The results of recently published studies potentially justify new recommendations for the use of RDN in clinical practice in appropriately selected patients in the new hypertension guidelines. The current review also summarizes the results of trials on RDN applied in another potential indication – atrial fibrillation. Six most important, prospective, randomized trials assessing RDN as adjunct therapy to pulmonary vein isolation for treatment of atrial fibrillation were discussed. In 5 studies, patients had uncontrolled BP despite treatment with three antihypertensive agents. The ratio for recurrence of atrial fibrillation for pulmonary vein isolation with RDN procedure was reduced by 57% as compared to pulmonary vein isolation (PVI) alone. BP was also reduced significantly after RDN in this subset of patients. Further multicenter studies involving standardized PVI and RDN procedures are needed.